Effect of flow direction on the conjugate heat transfer performance of LNG ambient air vaporizer with U-bend - Shanshan Liu; Wenling Jiao; Ping Zhang; Qi Li (Case Studies in Thermal Engineering)
Ambient air vaporizers (AAVs) with multiple U-shaped finned tubes are preferred for liquefied natural gas (LNG) vaporization due to their low energy consumption and eco-friendly nature. The flow direction significantly impacts vaporization efficiency and must be clarified for optimal design. This study develops a conjugate heat transfer model of an AAV tube module with a U-bend (ATMU), considering internal LNG flow boiling and two-way fluid-solid coupling with ambient air. Experiments using liquid nitrogen (LN2) were conducted to provide boundary conditions and validate the numerical model. The relative error between measured and simulated wall temperatures was within ±5 % when relative humidity was below 30 %. Results indicate that wall temperature does not increase monotonically along the flow direction due to interference between adjacent tubes and the U-bend. Numerical analysis shows that the natural convective heat transfer coefficient on the air side is 20 % higher for top inflow than for bottom inflow in the first half of the tube, resulting in superior heat transfer performance for AAVs with an initial top inflow of LNG. The optimal AAV installation aligns the overall LNG flow direction perpendicular to the annual prevailing wind at gas terminals, maximizing vaporization efficiency.